Apoptosis and tumour cell death in response to pro-apoptotic gene - Nik Abd Rahman, Nik Mohd Afizan; Allaudin, Zeenathul Nazariah; Mohamed Mustapha, Noordin; Ismail, Ruzila; Mustafa, Nor Hidayah; Mohd Lila, Mohd Azmi (Universiti Putra Malaysia Press, 2011)
The process of cell death, or apoptosis, is commonly defined by its distinct morphological characteristic. Apoptosis is considered a vital component of various processes including normal cell turnover, proper development and functioning of the immune system, the cellular antiviral response pathway, embryonic development and chemical-induced cell death. In this study, retroviral vector was utilized as the gene delivery vehicles and the tumour-specific viral death effector VP3 as pro-apoptotic agent for malignant colon cancer cells treatment. Here, pro-apoptotic gene inducing apoptosis in CT26 colon tumour cells is reported. In addition, the activation of a typical apoptotic programme was observed in response to this therapeutic agent. An increased number of colon tumour cells suffered apoptosis upon treatment with pro-apoptotic agent. As a result, these tumour cells displayed loss of membrane asymmetry and impermeability, cell shrinkage, nuclear condensation and DNA fragmentation under H&E images. In the presence of VP3, TEM also confirmed that VP3-treated CT26 tumour cells showed apoptotic features. These results suggested that VP3 was a potential pro-apoptotic agent and the apoptosis induced by VP3 was a key anti-tumour mechanism.